Analysis of the frontal recess pneumatization pattern in patients with chronic frontal sinusopathy - Krystal Calmeto Negri; Rogério Hamerschmidt; Cassio Iwamoto; Carolina Rodrigues Laranjeira Vilar (Brazilian Journal of Otorhinolaryngology)
Objectives: To analyze the pneumatization pattern of the frontal recess using CT scans and to determine the prevalence of frontoethmoidal cells and their possible correlation with the development of sinusopathy. Methods: By means of a retrospective, analytical and cross-sectional study, 300 CT scans of patients with clinical suspicion of chronic rhinosinusitis were examined, separately on the right and left sides, totaling a sample of 600 paranasal sinuses, with regard to the presence of frontal cells, the presence of blockage or veiling of the recess and frontal sinus. Results: Frontoethmoidal cells were present in 85.8% of cases; the most frequent cells were supra bulla cells, in 43.8%, and the least frequent were supraorbital ethmoid cells, in 11% of cases. There was a 35% prevalence of supra-Agger cells, 15.8% of supra-Agger frontal cells, 20.2% of supra bulla frontal cells and 12.3% of frontal septal cells. A significant relationship was found between the presence of supra-Agger frontal cells and supra bulla frontal cells and the development of sinusopathy. Conclusion: The supra-Agger frontal cells and supra bulla frontal cells, when present in the frontal recess, predispose to the development of frontal sinusopathy. Therefore, preoperative tomographic analysis allows a three-dimensional anatomical understanding of the recess and frontal sinus based on determining the pneumatization pattern of this region. Level of evidence: Level 3.